2013
DOI: 10.1002/jrs.4425
|View full text |Cite
|
Sign up to set email alerts
|

A SERS‐active enzymatic product used for the quantification of disease‐related molecules

Abstract: In this paper, a method for enhancing the analysis of biologic materials was designed. This method incorporated the surfaceenhanced Raman scattering (SERS) technique and an enzyme catalysis-based bioassay to develop a more efficient analysis procedure. Using this combination, the quick and simple detection of disease-related molecules (the human cardiac isoform of troponin T, cTnT) in human serum was achieved. This method utilizes enzyme catalysis to develop a H 2 O 2 -horseradish peroxidase (HRP)-3,3′,5,5′-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…As well as the lines observed on the curve (c) (Figs. 3 and 4) which are typical for proteins, appear due to SERS (in previous publications, [32][33][34][35] dedicated to ChOX the oscillation spectra are not presented). It is well known 15,16 that when the size of nanoparticles is reduced, the lines amplitude is increased.…”
mentioning
confidence: 93%
“…As well as the lines observed on the curve (c) (Figs. 3 and 4) which are typical for proteins, appear due to SERS (in previous publications, [32][33][34][35] dedicated to ChOX the oscillation spectra are not presented). It is well known 15,16 that when the size of nanoparticles is reduced, the lines amplitude is increased.…”
mentioning
confidence: 93%
“…In this work, we described results from AChE experiments, but it is obvious that many other enzymes can be monitored in a similar fashion [51]. The key is finding proper enzyme substrates whose SERS activity can be switched on or "unmasked" upon the enzyme activity, and the end product exhibits a high affinity toward a noble metal surface [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Three main Raman bands corresponding to oxTMB could be observed at 1608 cm -1 , 1336 cm -1 and 1190 cm -1 (Fig. 1c), which could be attributed to ring stretching and C-H bending, inter-ring C-C stretching and CH 3 bending, respectively 22 and provided evidence that a blue CTC had occurred, due to the oxidation of TMB 20 . In addition, another Raman band at 1401 cm -1 was observed in the fingerprint spectra of oxTMB from the stretching vibration of N=N, as a result of azo compound or unoxidized TMB, which was also enhanced by the presence of AuNSt 21 .…”
Section: Characterisation Of Aunst As Catalysts and Raman Enhancersmentioning
confidence: 97%
“…their sharp tips, could produce phenomenal Raman enhancement [15][16][17] and therefore, they have also been exploited for the design of SERS-sensors for Hg 2+ detection 18,19 . Unlike previously reported research, the presented mechanism involves the catalytic activity of AuNSt for the oxidation of 3,3',5,5'-tetramethybenzidine (TMB) in the presence of H 2 O 2 to produce oxidised TMB (oxTMB), a highly Raman active product [20][21][22] . We observed that in the presence of Hg 2+ ions, the Au-Hg amalgamation could even enhance the catalysed oxidation reaction as evident by the strong blue coloured oxTMB product.…”
Section: Introductionmentioning
confidence: 97%